Recent Advances on Asymmetric Synthesis of Dihydroflavones - Du, Zhihao; Li, Guojing; Dai, Wenhao; Liu, Yu (Pharmaceutical Fronts, 2025)
Dihydroflavones, as an important part of flavonoid compounds, possess a wide range of physiological activities and significant medicinal values. The importance of these compounds has driven the research on the preparation of dihydroflavonoid compounds, and many chiral dihydroflavonoid compounds can be obtained with potential activity, excellent yields, and stereoselectivity using various effective synthetic strategies. This paper reviews the biological activities of single-configuration chiral flavanones and provides a comprehensive overview of the research progress in the asymmetric synthesis of this group of flavonoids from 2002 to 2024, including (1) synthesis from ortho-hydroxy chalcones, (2) synthesis from chromones, (3) asymmetric reduction, (4) intramolecular Mitsunobu and carbene insertion. These methods provide some efficient and economical synthetic strategies for the asymmetric synthesis of flavanones, especially in enantioenriched aspects.
Keywords: enantiomeric activity; chiral dihydroflavone; asymmetric catalysis